VARIASI KESANTUNAN PENGGUNAAN UNGKAPAN PERMOHONAN MAAF DALAM BAHASA JEPANG - Akhmad Saifudin (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2009)
This writing analyzes the issue of selecting politeness variation in Japanese apology. This research is focused on the Japanese socio-cultural factors which arises the use of politeness variation in Japanese apology. The source of data was taken from the transcript of a drama serial entitled Oshin which was produced by Sugako Hashida. The data are 6 forms of apologizing, they are sumimasen, sumanee, gomenshitekureno, mooshiwakearimasendeshita, mooshiwakegozaimasen, and owabiitashimasu. Apalogizing is carried out as to maintain a harmonious social interaction. Socio-cultural factors are social status difference factor (vertical), social distance factor (horizontal), formality, and value from mistakes which are produced by the user. The use of politeness variation is aimed to smooth and minimize the speakers’ mistakes.